A guide to plant TPX2-like and WAVE-DAMPENED2-like proteins. (1st November 2020) - Smertenko, Andrei; Clare, Shaun J; Effertz, Karl; Parish, Alyssa; Ross, Austin; Schmidt, Sharol
Abstract : The TPX2 protein family comprises WAVE-DAMPENED2-like (WDL) and TPX2-like (TPXL) groups. WDLs govern cell expansion in response to ethylene, light, brassinosteroids, and abiotic stresses. TPXLs function in mitotic spindle assembly and activating Aurora kinase. Abstract: TPX2 proteins were first identified in vertebrates as a key mitotic spindle assembly factor. Subsequent studies demonstrated that TPX2 is an intricate protein, with functionally and structurally distinct domains and motifs including Aurora kinase-binding, importin-binding, central microtubule-binding, and C-terminal TPX2 conserved domain, among others. The first plant TPX2-like protein, WAVE-DAMPENED2, was identified in Arabidopsis as a dominant mutation responsible for reducing the waviness of roots grown on slanted agar plates. Each plant genome encodes at least one 'canonical' protein with all TPX2 domains and a family of proteins (20 in Arabidopsis) that diversified to contain only some of the domains. Although all plant TPX2-family proteins to date bind microtubules, they function in distinct processes such as cell division, regulation of hypocotyl cell elongation by hormones and light signals, vascular development, or abiotic stress tolerance. Consequently, their expression patterns, regulation, and functions have diverged considerably. Here we summarize the current body of knowledge surrounding plant TPX2-family proteins.